PENERAPAN PUZZLE GEMPA BUMI DAN TSUNAMI UNTUK MENINGKATKAN PENGETAHUAN PENGURANGAN RISIKO BENCANA PADA SISWA KELAS V SD NEGERI 15 BANDA ACEH - Aswadi .; Khairuddin .; Alamsyah Taher (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Knowledge is always used as the beginning of a person's actions and consciousness. So with the knowledge capacity is expected to be the basis of a person's actions. Media puzzle earthquake and tsunami is a medium that can be used as a reference for teachers as a variation in the learning process. Disaster risk reduction knowledge necessary for children to be able to respond quickly and proactively to catastrophic events. Application of the puzzle in disaster risk reduction can be done by providing a range of different cognitive knowledge to children living in disaster-prone areas. For this study, researchers used experimental study. The research location was the State Primary School No. 15 Banda Aceh, conducted in March 2016. The population in this study was all students who were in year of 24 students. The test used is the right hand, then